PEECO a sustainable plant-feeding waterless men's public urinal system for pedestrians - Garcia, Patrick P.
Water pollution and water shortage are some of the problems that we humans face with our growing population. We use every day products and systems that contribute to environmental problems that we experience today, and urinals are part of them. Human excreta are waste products which are disposed of every day in our society. Every day, together with getting rid of excreta, are the nutrients that are flushed away with drinkable water, either to be treated at high cost or discharged to different bodies of waters. Instead of serving as sources of nutrients, these waters even add to water pollution instead of utilizing it for beautiful landscapes and food production. Excreta in the form of pure urine have more volume and fertilization value compared to feces. If urine were to be viewed as a resource rather than a waste product, and if proper planning is implemented, we could help save drinkable water and lessen water pollution to improve the well-being of men and our planet. A sustainable and eco-friendly urinal that does not use water in flushing away urine and does not add to water pollution can be a part of an effective solution to some of these environmental problems we face. The main point of the design solution is the plan of a waterless urinal system that incorporates plant boxes which harness the nutrients from on-site filtration of urine to be able to grow plants. Urine deposited into urinal will be filtered by pebbles, activated charcoal and crushed limestone. The filtered urine will then be used as the main source of nutrients for plants, aside from sunlight and occasional rain pour. By combining different forms [of] green technology that are already available, plus innovations in materials and sustainable design, urine can become a resource rather than waste. The design is a step for creating an eco-friendly environment.